Simian-Human Immunodeficiency Virus SHIV.C.CH505 Persistence in ART-Suppressed Infant Macaques Is Characterized by Elevated SHIV RNA in the Gut and a High Abundance of Intact SHIV DNA in Naive CD4(+) T Cells - Obregon-Perko, Veronica (J Virol, 2020)
Mother-to-child transmission of human immunodeficiency virus type 1 (HIV-1) continues to cause new pediatric cases of infection through breastfeeding, a setting where it is not always possible to initiate early antiretroviral therapy (ART). Without novel interventions that do not rely on daily ART, HIV-1-infected children face lifelong medications to control infection. A detailed analysis of virus persistence following breast milk transmission of HIV-1 and ART has not been performed. Here, we used infant rhesus macaques orally infected with simian/human immunodeficiency virus (SHIV) (SHIV.C.CH505) to identify cellular and anatomical sites of virus persistence under ART. Viral DNA was detected at similar levels in blood and tissue CD4(+) T cells after a year on ART, with virus in blood and lymphoid organs confirmed to be replication competent. Viral RNA/DNA ratios were elevated in rectal CD4(+) T cells compared to those of other sites (P ≤ 0.0001), suggesting that the gastrointestinal tract is an active site of virus transcription during ART-mediated suppression of viremia. SHIV.C.CH505 DNA was detected in multiple CD4(+) T cell subsets, including cells with a naive phenotype (CD45RA(+) CCR7(+) CD95(–)). While the frequency of naive cells harboring intact provirus was lower than in memory cells, the high abundance of naive cells in the infant CD4(+) T cell pool made them a substantial source of persistent viral DNA (approximately 50% of the total CD4(+) T cell reservoir), with an estimated 1:2 ratio of intact provirus to total viral DNA. This viral reservoir profile broadens our understanding of virus persistence in a relevant infant macaque model and provides insight into targets for cure-directed approaches in the pediatric population. IMPORTANCE Uncovering the sanctuaries of the long-lived HIV-1 reservoir is crucial to develop cure strategies. Pediatric immunity is distinct from that of adults, which may alter where the reservoir is established in infancy. Thus, it is important to utilize pediatric models to inform cure-directed approaches for HIV-1-infected children. We used an infant rhesus macaque model of HIV-1 infection via breastfeeding to identify key sites of viral persistence under antiretroviral therapy (ART). The gastrointestinal tract was found to be a site for low-level viral transcription during ART. We also show that naive CD4(+) T cells harbored intact provirus and were a major contributor to blood and lymphoid reservoir size. This is particularly striking, as memory CD4(+) T cells are generally regarded as the main source of latent HIV/simian immunodeficiency virus (SIV) infection of adult humans and rhesus macaques. Our findings highlight unique features of reservoir composition in pediatric infection that should be considered for eradication efforts.